Development of the Mobile-Based NAMISIKU Application for Early Detection of Postpartum Depression - Syarif, Syastriani Isna Putri; Pabokori, Sudirman; Anita, Anita (Universitas Aisyah Pringsewu, 2024)
Psychological changes in pregnant women tend to be less apparent and often become more evident during the postpartum period. This study is a development research using a Research and Development (RD) design with the ADDIE model (Analysis, Design, Development, Implementation, and Evaluation) as the framework for designing and developing the product. The main features developed and integrated into the application include a depression assessment questionnaire based on a clinically recognized scale, namely the Edinburgh Postnatal Depression Scale (EPDS), mental health tips and information, as well as access to resources and professional support. This research was conducted in the working area of Sorawolio Public Health Center. The application testing involved 14 respondents, consisting of all midwives at Sorawolio Public Health Center in Baubau City. The results showed that the application performed excellently in terms of attractiveness, perspicuity, and novelty, thus providing a positive user experience. However, the low score in dependability indicates system reliability issues that need to be addressed before the application is widely launched.